2020
DOI: 10.1177/2382120520964852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hands-on Pre-Clinical Neurosurgery Elective Course on Second-Year Medical Student Interest and Attitudes

Abstract: Introduction: Medical student involvement opportunities and educational experiences with surgical residents during medical school have been shown to increase the chance of students deciding to specialize in surgical specialties. This study aims to determine the effect of a neurosurgery elective during the second preclinical year on student interest and opinion of neurosurgery. Methods: Thirty-nine students completed opinion-based surveys and factual knowledge quizzes during a neurosurgical elective course over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…That mentioned, such exposure may aid in waving the frequently overestimated negative assumptions on neurosurgical specialty, especially in institutes which were primary care and nonsurgical specialties are being emphasized on during the medical students’ early clinical years. [ 18 , 21 ] In our study, we found that medical students with closer exposure to neurosurgery had a rather better understanding the specialty and were more likely to have neurosurgery as their career choice. Around 6% of all study participants had a more dedicated exposure to the neurosurgery in the form of attending neurosurgical conferences and were involved in neurosurgery-related research projects, and this correlated with statistical significance to interest in neurosurgery.…”
Section: Discussionmentioning
confidence: 55%
“…That mentioned, such exposure may aid in waving the frequently overestimated negative assumptions on neurosurgical specialty, especially in institutes which were primary care and nonsurgical specialties are being emphasized on during the medical students’ early clinical years. [ 18 , 21 ] In our study, we found that medical students with closer exposure to neurosurgery had a rather better understanding the specialty and were more likely to have neurosurgery as their career choice. Around 6% of all study participants had a more dedicated exposure to the neurosurgery in the form of attending neurosurgical conferences and were involved in neurosurgery-related research projects, and this correlated with statistical significance to interest in neurosurgery.…”
Section: Discussionmentioning
confidence: 55%
“…According to previous studies, early exposure of students to cadaver practice, surgery, and hands-on practice modules effectively increases their interest in neurosurgery. [4][5][6][7][8]11,13,18] Furthermore, most of these exposures were targeted at students who volunteered to participate or were already interested in neurosurgery. While such focused education is effective, Zoli et al suggested that neurosurgical education and training should involve all students.…”
Section: Discussionmentioning
confidence: 99%
“…24 A last example is the University of Pittsburgh School of Medicine, which instituted a preclinical elective course for 2nd-year students that was designed by residents, senior students, and attendings. 25 This course was correlated with higher chances of choosing neurosurgery as a career, an increased understanding of the discipline, and higher knowledge scores after the elective. 25 The opportunities these schools have provided to network, perform research, and learn about the field and more is priceless when preparing a residency application.…”
Section: Lack Of Presence At Feeder Medical Schools and Hindrance Of ...mentioning
confidence: 94%
“…25 This course was correlated with higher chances of choosing neurosurgery as a career, an increased understanding of the discipline, and higher knowledge scores after the elective. 25 The opportunities these schools have provided to network, perform research, and learn about the field and more is priceless when preparing a residency application. However, since Black/African American medical student enrollment is lower at these feeder programs, many Black/African American medical students do not have these connections or possibilities to improve their residency application to neurosurgery.…”
Section: Lack Of Presence At Feeder Medical Schools and Hindrance Of ...mentioning
confidence: 94%